Response of soybean plants to gamma radiation: Biochemical analyses and expression patterns of trichome development - Suludere, Zekiye; ATAK, ÇİMEN; ÇELİK, ÖZGE (My University, 2014)
This is the first report on soybean with the aim to show the effects of gamma radiation on trichome metabolim. Soybean seeds were subjected to 300 Gy gamma radiation at a dose rate of 10 Gy/min using a Cs-137 gamma source. The photosynthetic pigment, total protein content and ascorbate peroxidase activity were studied. The results showed that the chlorophyll a content was decreased by 80% on day 14 and by 77% on day 21 of irradiation. The chlorophyll b content was reduced by 58.6% and 62.06% on day 14 and 21 after irradiation, respectively. The total carotenoid concentration was reduced by 81.14% on the 14th day after irradiation and by 91% on the 21st day of irradiation, compared to control. The total protein concentration was found to have decreased significantly at 14 and 21 day after treatment. High level of ascorbate peroxidase (APX) activity was recorded in the leaves developed from irradiated soybean seeds, compared to the non-irradiated group. The trichome densities were 6.76 fold increased at 21 day of irradiation, while the stomatal densities were decreased, compared to control. We also performed a qRT-PCR analysis to detect the transcription levels of the soybean trichome developmental genes. The GL2 and CPC genes were up-regulated (P≤0.05). The results of this study pointed out that the CPC transcription factor has to be study in further studies to provide an insight on its exact role in regulation of trichome development in soybean under radiation stress.
Keywords: Gamma radiation; Glycine max; trichome; ortholog genes; qRT-PCR